Efektivitas Kaporit dalam Menurunkan Kadar Amoniak dan Bakteri Koliform dari Limbah Cair RSUD Tugurejo Semarang - Mariyana Mariyana; Tri Joko; Nurjazuli Nurjazuli (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Tugurejo Hospital Semarang is one of hospital that treats liquid waste by providing chlorine to kill microorganisms and decrease ammonia. Ammonia in water will react with chlorine and monochloramin, dichloramin, or tichrolamin. The purpose of this study was to determine the effectiveness of chlorine in the ability to reduce levels of ammonia and coliform bacteria in wastewater Tugurejo Hospital Semarang. The independent variable of this study is variations of chlorine dose, and dependent variable is the level of ammonia and coliform bacteria. This type of research is experiment. The population that used is wastewater that is in the indicator tub of WWTP (wastewater treatment plant) Tugurejo Hospital Semarang. The samples in this study were hospital wastewater taken from Tugurejo Hospital Semarang tank before chlorination. Level of ammonia before the treatment are 3,16 mg/l. After give the variations dose of chlorine 3 gr/l level ammonia decreas until 98,51% be 0,05 mg/l. Test one way annova was obtained value of p < 0.05 then Ho was received, which means there is an average differentiationof ammonia decreased levels in wastewater Tugurejo Hospital Semarang by administering thevariation dose of chlorine. The results of measurements of coliform bacteria in wastewater Tugurejo Hospital Semarang after giving the variation dose showed that all treatments chlorine dosing < 3 which means negative or there is none coliform bacteria in wastewater. The effective chlorine dose for lowering the levels of ammonia is 3 g/l and on the 1 gr/l dose of chlorine, it can decreas the coliform bacteria. Is suggested chlorine indicator is given to the last bath before entering the outlet.